2019
DOI: 10.12669/pjms.35.1.280
|View full text |Cite
|
Sign up to set email alerts
|

The role of Endocan as a Prognostic Biomarker in community-acquired pneumonia

Abstract: Objective: The aim of this study was to determine the importance of using endocan as a biomarker in deciding the setting of treatment and predicting prognosis in patients with community-acquired pneumonia (CAP). Methods: This prospective, case-control study was conducted at Okmeydani Training and Research Hospital between November 20, 2016 to March 20th 2017. Blood samples were obtained from 63 patients who were admitted to internal medicine clinic due to CAP and 25 volunteers without active infection. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In the present study, the baseline characteristics of CAP and short term mortality rates were consistent with previous studies on CAP in Turkey [5][6][7]. However, in a multicenter retrospective study, Erdem et al reported that 30-day mortality rate was %31.2 (n=129/413) in patients with severe CAP [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, the baseline characteristics of CAP and short term mortality rates were consistent with previous studies on CAP in Turkey [5][6][7]. However, in a multicenter retrospective study, Erdem et al reported that 30-day mortality rate was %31.2 (n=129/413) in patients with severe CAP [10].…”
Section: Discussionsupporting
confidence: 91%
“…Limited data exist on post discharge long-term outcomes and its predictors [4][5][6], although short-term prognostic predictors for CAP were well studied in Turkey [7][8][9][10]. In this study, we aimed to determine the indicators for poor short-term and long-term outcomes in older adults with CAP requiring hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“… Alavi-Moghaddam et al, 2013 [ 20 ], Ozkan et al, 2020 [ 21 ], Fuchs Bahlis et al, 2021 [ 2 ], Esteban Ronda et al, 2021 [ 22 ], Feng et al, 2021 [ 3 ], Lazar Neto et al, 2021 [ 6 ], Estella, 2015 [ 23 ], Demirel, 2018 [ 24 ], Holten et al, 2020 [ 25 ], Olivia et al, 2021 [ 26 ], Cupurdija et al, 2015 [ 27 ], Anurag and Preetam, 2021 [ 5 ], Ranzani et al, 2017 [ 28 ], Günaydın et al, 2019 [ 29 ], Tsai et al, 2021 [ 30 ], Wen et al, 2020 [ 31 ], Putot et al, 2016 [ 7 ], Wang et al, 2020 [ 32 ], Bloom et al, 2019 [ 33 ], Williams et al, 2018 [ 34 ], Kim et al, 2013 [ 10 ], Aydin et al, 2019 [ 35 ], Akpınar et al, 2019 [ 36 ], Ito et al, 2017 [ 37 ], Lee et al, 2013 [ 38 ] …”
Section: Reviewmentioning
confidence: 99%
“…A comparison was made for the highest classes for both severity scores in 13 studies [ 6 , 7 , 20 - 22 , 25 , 27 - 29 , 31 , 34 , 37 , 38 ]. Ozkan et al’s [ 21 ] study had 66.7%/88.9, Alavi-Moghaddam et al [ 20 ] 96.7%/90%, Esteban Ronda et al [ 22 ] 84.62%/88.46%, Lazar Neto et al [ 6 ] 59.9%/56.0%, Holten et al [ 25 ] 71%/58%, Cupurdija et al [ 27 ] 22%/29%, Ranzani et al [ 28 ] 92%/78%, Günaydın et al [ 29 ] 85.2%/82.4%), Wen et al [ 31 ] 66%/85%, Putot et al [ 7 ] 66%/58%, Williams et al [ 34 ], 98%/94%, Ito et al [ 37 ] 24.9%/17.9, and Lee et al [ 38 ] 40.0%/50.0% for PSI and CURB-65 mortality predictions, respectively. The mortality rate for PSI class V ranged from 60% to 96%.…”
Section: Reviewmentioning
confidence: 99%
“… 4 , 5 Recent studies have found that the onset and progression of COPD has a certain correlation with the intestinal microenvironment. 6 , 7 Research has shown that microbial colonies are not only distributed in the intestines, but also in the lungs, with a “gut-lung” axis connection. 8 Disturbance of the gut microbiota not only affects the gastrointestinal immune response but may also have a negative impact on immune states of other organs including lungs.…”
Section: Introductionmentioning
confidence: 99%